The Influence of retained earnings on financial performance of listed manufacturing and allied firms in Kenya - Lumbasio, Ayiego Jackson; Ronald, Martin Onsiro; Abuga, Isaac Mukono (Universitas Nahdlatul Ulama Surabaya, 2025)
This study assessed the influence of retained earnings on financial performance of listed manufacturing and allied firms in Kenya. The study covered a period between 2016 and 2023. The descriptive survey design was utilized in this research. The target population included 10 manufacturing firms listed on the NSE from 2016 to 2022 while respondents comprised all 248-line managers within the target population. Data collection method utilized was both secondary and primary. The study found out that retained earnings has a highly significant influence on financial performance, with a correlation coefficient of 0.885 and an adjusted R squared of 0.653, suggesting that retained earnings decisions are critical for optimizing profitability in listed manufacturing and allied firms in Kenya. The moderating effect of ownership on the relationship between retained earnings and financial performance was also found to be significant, with a correlation coefficient of 0.580 (p value<0.05) and an increase in the model's explanatory power by 5 percent. Retained earnings serve as a valuable internal financing source, supporting growth and innovation while enhancing financial stability. The moderating effect of ownership structures, especially those involving government or institutional stakeholders, is essential for optimizing capital strategies and improving financial outcomes.